2014
DOI: 10.1177/1753944714553226
|View full text |Cite
|
Sign up to set email alerts
|

The role of chronic hyperviscosity in vascular disease

Abstract: BackgroundThe pathogenesis of vascular disease is complex and as of yet not totally understood. Conventional wisdom suggests that atherosclerotic cardiovascular disease is caused by the accumulation of lipid molecules in the arterial luminal wall. Various therapeutic modalities have been proposed; however, current treatment with cholesterol-lowering drugs has not completely solved this problem. Risk factors aiding in the development of atherosclerotic disease have been long promoted, such as genetics, dyslipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 34 publications
1
41
0
5
Order By: Relevance
“…Decreased vascular resistance due to the arterial dilatation may develop in subjects with anemia. Besides, decreased blood viscosity due to the decreased hematocrit level can improve circulation [12,13]. In accordance with this link, hypertensive patients with BTM presented with a better 24-h blood pressure profile compared to patients without BTM [14].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Decreased vascular resistance due to the arterial dilatation may develop in subjects with anemia. Besides, decreased blood viscosity due to the decreased hematocrit level can improve circulation [12,13]. In accordance with this link, hypertensive patients with BTM presented with a better 24-h blood pressure profile compared to patients without BTM [14].…”
Section: Discussionsupporting
confidence: 54%
“…Baserga et al [15] reported a lower incidence of hypertension in subjects with BTM. Additionally, a high hemotocrit percentage and policythemia have been reported to be associated with a high blood pressure in other studies [12,16].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased blood viscosity is associated with many forms of cardiovascular disease. [24][25][26] In animals, pathologic increases in blood viscosity are seen with severe dehydration and hemoconcentration, as well as with polycythemia and some hyperglobulinemias. These conditions lead to obvious perfusion deficits, and are occasionally encountered in surgical patients.…”
Section: Anemia and Oxygen Deliverymentioning
confidence: 99%
“…Согласно современным представлениям, важную роль в появлении и прогрессировании АГ играет нарушение реологических свойств крови [2]. В экс-периментальных и клинических исследованиях было убедительно показано прямое и косвенное участие гемореологического фактора в механизмах формиро-вания повышенного АД [3].…”
unclassified
“…Как известно, системное АД зависит от двух физиологических переменных: сердечного выброса и общего периферического сопротивле-ния сосудов (ОПСС) [2]. Поэтому при разработке методов коррекции АГ бóльшее внимание врачей уделяется, как правило, контролю сосудистого тонуса и работы сердечной мышцы пациентов.…”
unclassified